Peripheral Giant Cell Granuloma in 9-Year-Old Female Patient - Patel, Jalark Chimanbhai; Sujan, Sunanda Gul; Deshpande, Anshula Neeraj; Dave, Bhavna H (Journal of Orofacial Research, 2013)
The peripheral giant cell granuloma (PGCG) is a benign hyperplastic gingival lesion of unknown etiology occurring mostly in adults. However, it is less commonly seen in females withpreponderance for fifth and sixth decade of the life. It is clinically difficult to distinguish PGCG from pyogenic granuloma, fibrous epulis or irritation fibroma. This article presents a case with exophytic gingival lesion in 9 years old female patient. This lesion was interfering with functions and altering the esthetics. It is a challenge for the clinician to manage such type of pathologies in young children.